Internal waves excited by the Marangoni effect - Wierschem, Andreas; Linde, Hartmut; Velarde, Manuel (Physical Review E, 2000)
Traveling periodic internal wave trains are generated in liquid layers during the absorption process of a miscible surface-active substance out of the vapor phase. In our nonstationary experimental runs, internal waves are excited by surface waves, which had been previously generated by a surface-tension-gradient-driven instability. The internal wave trains adjust their wave number by an Eckhaus instability. Close to the instability threshold narrow and extended pulses are observed. Furthermore, the wave trains can alter their traveling direction, i.e., one wave train traveling in one direction yields to another train, in general of different wave number, traveling in the opposite direction. ©2000 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2000.tech.ITC.stmmec.intern